2018
DOI: 10.1111/cid.12657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different maintenance time of torque application on detorque values of abutment screws in full‐arch implant‐supported fixed prostheses

Abstract: The application of 35 N-cm for different maintenance time of torque application on implant abutment screw did not appear to affect the detorque value in a multiple implant-supported fixed prosthesis. Maintaining the torque for prolonged time (10 seconds or 30 seconds) was not significantly associated with higher preload than instant torque application in full-arch implant-supported prosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The results of Jorge et al and Al-Otaib et al [ 38 , 44 ] corroborate those of previous studies, which found that all detorque values were lower than the insertion torque in the baseline in the external hexagon connection and Morse taper (Jorge et al) and the internal connection (Al-Otaibi et al). The loss of torque loss a few minutes after torque application is expected and can be explained by a phenomenon known as the sedimentation effect or embedment relaxation [ 25 , 54 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The results of Jorge et al and Al-Otaib et al [ 38 , 44 ] corroborate those of previous studies, which found that all detorque values were lower than the insertion torque in the baseline in the external hexagon connection and Morse taper (Jorge et al) and the internal connection (Al-Otaibi et al). The loss of torque loss a few minutes after torque application is expected and can be explained by a phenomenon known as the sedimentation effect or embedment relaxation [ 25 , 54 ].…”
Section: Discussionsupporting
confidence: 86%
“…Static mechanical behavior after one tightening was evaluated in two studies: Jorge et al 2013 and Al-Otaibi et al 2018 [ 38 , 44 ]. A torque of 35 Ncm was applied to the abutment screw in the study of Al-Otaibi et al; an insertion torque of 20 or 30 Ncm, recommended by the manufacturer, depending on the abutment, was applied by Jorge et al Retention screws received insertion torque; after 3 min, the initial detorque was measured using a torque gauge by Jorge et al Al-Otaibi et al used three protocols in which abutment screws were subjected to different maintenance of torque application (instant, 10 s, 30 s), and the removal torque value (RTV) was recorded with a digital torque gauge.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The abutment material could influence the joint stability [5]. In the present study, torque maintenance was tested using digital torque meter device [22][23][24]. There were no significant differences regarding the mean torque loss values between the three groups.…”
Section: Discussionmentioning
confidence: 80%